Development of bugs reporting system for home pricing / Fazrul Shah Ab. Karim - Ab. Karim, Fazrul Shah (2004)
Data and information in an organization are the most essential components which needed to manage properly to ensure for the stability of the work process in the management environment. These components can help to increase the organization effectiveness and reliability in data processing. This project is been implement for Nisasol Sdn.Bhd company under Administration Department which located at Damansara Utama Petaling Jaya. This company had developed a system called Home Pricing and use the manual reporting to report bugs or error in this system. A new computerised system called Bugs Reporting System was developed to replace the manual reporting process. The main objective of implementing this system is to automate the processes of sending report by the users and receiving it by the system administrator. It is also helps the system administrator to maintain the report log and for references in the future. For the user, reporting the bugs and error become easily and the responds process will be faster than the manual system. This project was developed by using an open source tools, which include the Apache web server, PHP scripting language and the MySQL relational database management system.